Low-temperature hydrogen production and consumption in partially-hydrated peridotites in Oman: implications for stimulated geological hydrogen production - Templeton, Alexis S.; Ellison, Eric T.; Kelemen, Peter B.; Leong, James; Boyd, Eric S.; Colman, Daniel R.; Matter, Juerg M. (Frontiers in Geochemistry, 2024)
Department of Energy recently allocated funding to investigate stimulated H2 production using various stimuli, as well as characterization of the properties of target source rocks and reservoirs (U.S. Department of Energy, 2023aEnergy, , 2023b)).Numerous potential Fe(II)-bearing source rocks may yield some hydrogen during water/rock reaction, although many protoliths have not yet been carefully tested. Equilibrium thermodynamic models can be used to predict potential hydrogen yields. The best targets for stimulated hydrogen production are rocks such as peridotites, which can produce 2-4 kg hydrogen/m 3 of rock, up to 4-orders of magnitude more hydrogen than mafic rocks such as basalts (Bach, 2016; Leong et al., 2021a;Osselin et al., 2022;Ely et al., 2023). For serpentinization of ultramafic rocks, the integrated set of reactions that couple the oxidation of mineral-derived Fe(II) to the reduction of water to produce hydrogen gas are predicted to occur at maximum extents at temperatures between 200-300 o C (McCollom and Bach, 2009;Klein et al., 2013). However, reaching these high temperatures in an engineered system requires either initiating water/rock reactions at great depth, or adjacent to hydrothermally-active geological systems, or in rocks heated by large inputs of energy. However, it is notable that hydrogen naturally occurs in seeps and groundwaters in shallow ultramafic rock formations, leading to the possibility that some hydrogen producing reactions do proceed at temperatures ≤100 o C. This hydrogen flux may be sustained through active water/rock reactions, or may be derived from fossil hydrogen produced at depth and stored within the peridotite. Locations on Earth where abundant hydrogen has been measured in seeps and groundwaters emanating from ultramafic rocks include the Phillipines (Abrajano et al.